SYNTHESIS AND STRUCTURAL CHARACTERIZATION OF ZNO NANOPARTICLES - ASAULYUK, Tatyana; SARIBYEKOVA, Yulia; SEMESHKO, Olga; KULISH, Irina (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In the present work, zinc oxide (ZnO) nanoparticles were synthesized by direct precipitation method in aqueous solution using zinc acetate dihydrate and sodium hydroxide as precursors. The molar ratio of Zn2+ to OH- was 1:2. The obtained precipitated compound was treated at different temperatures. The crystal phase and structural parameters of each prepared ZnO samples such as interplanar spacing, crystallite size, dislocation density, micro strain were determined by X-ray diffraction (XRD) analysis for different crystallographic planes. Other crystallite parameters such as lattice constants, unit cell volume, Zn–O bond length, crystallinity of synthesized ZnO samples also were calculated from the XRD data. The XRD patterns show the successfully synthetized ZnO phase with wurtzite hexagonal structure and average crystallite sizes of 24.6 nm, 25.6 nm and 28.1 nm for the samples that dried at room temperature without heat treatment (S1), dried at 60°C without calcination (S2), dried at 60°C and calcinated at 300°C in air atmosphere for 2 hours (S3) respectively. The calculated structural parameters of the synthesized ZnO nanoparticles are in good agreement with the standard reported data (JCPDS 36-1451). The effect of heat treatment on the structural parameters of synthesized ZnO nanoparticles was examined and it indicates that increasing the thermal decomposition temperature improves the quality of crystalline material. The XRD data show that the synthesized S3 sample was free of impurities and characterized by lattice constants a = 3.252 Å, c = 5.210 Å, unit cell volume V = 47.703 Å3, bond length Zn–O = 1.9789 Å and crystallinity 93%. The results are of practical value for simple synthesis of highly dispersed forms of ZnO and its possible application in textile finishing.
Keywords: ZnO; nanoparticles; precipitation; structure; XRD